Ujaran Kebencian Netizen Pendukung Anies terhadap Prabowo di Media Sosial X Kajian Pragmatik Linguistik Forensik: Penelitian - Abdullah, Miranda; N. Djou, Dakia; Umam Kau, Munkizul (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to examine the forms of hate speech and the types of speech acts used by netizens who support Anies Baswedan against Prabowo Subianto on the social media platform X (formerly Twitter), particularly in the context of the 2024–2029 Indonesian presidential election. A qualitative descriptive approach was employed, using data collected through screenshots of tweets containing hate speech. The analysis was conducted using speech act theory proposed by Austin and Searle, as well as hate speech frameworks developed by Benesch and Matsuda. The findings reveal that the most dominant forms of hate speech include insults, defamation, provocation, blasphemy, and the spread of false information. These expressions are delivered through various speech acts such as locutionary, illocutionary, and perlocutionary acts. The most frequently found types are expressive illocutionary acts (expressing hatred and anger) and directive illocutionary acts (calling others to reject or act). The study concludes that hate speech functions not only as an ideological or emotional expression but also has serious social and legal implications. This research contributes to a better understanding of hate speech patterns in digital discourse and supports the development of forensic linguistics, while also promoting legal and communication literacy in society.